Investigation about Electrorheological Squeeze Film Damper Applied to Active Control of Rotor Dynamic - Benjamin Pecheux; Olivier Bonneau; Jean Frêne (International Journal of Rotating Machinery)
Electrorheological (ER) fluids, discovered in 1947 by W. WINSLOW, are concentrated suspensions of solid particles in an oily base liquid. Exposed to a strong electric field, their resistance to flow increases very greatly and this change is progressive, reversible and occurs very rapidly. Nowadays, ER fluids, made of lithium salt and fluorosilicon got rid of their old abrasive characteristics and are able to provide a good interface between electronics and mechanical components. A bibliographical study on ER fluids and ER technology has been carried out. The aim of this study is adapting ER technology to Squeeze Film Damper. In order to provide an active control on a flexible rotating shaft so as to command the whole shaft/bearings device in case of high rotating speed or heavy load trouble. Results of numerical computation of a shaft bearing assembly with a Squeeze Film Damper using negative ER fluid are showed in order to see the possibility of avoiding critical speeds by natural frequency shifting. A technical study of ER Squeeze Film Damper design is also presented, taking into account ER fluid properties and ER technology requirements.